Using Experimental Research Designs to Explore the Scope of Cumulative Culture in Humans and Other Animals. (30th October 2018) - Caldwell, Christine A.
Abstract: In humans, cultural evolutionary processes are capable of shaping our cognition, because the conceptual tools we learn from others enable mental feats which otherwise would be beyond our capabilities. This is possible because human culture supports the intergenerational accumulation of skills and knowledge, such that later generations can benefit from the experience and exploration efforts of their predecessors. However, it remains unclear how exactly human social transmission supports the accumulation of advantageous traits, and why we see little evidence of this in the natural behavior of other species. Thus, it is difficult to know whether the cognitive abilities of other animals might be similarly scaffolded by processes of cultural evolution. In this article, I discuss how experimental studies of cultural evolution have contributed to our understanding of human cumulative culture, as well as some of the limitations of these approaches. I also discuss how similar research designs can be used to evaluate the potential for cumulative culture in other species. Such research may be able to clarify what distinguishes human cumulative culture from related phenomena in nonhumans, shedding light on the issue of whether other species also have the potential to develop cognitive capacities that are outcomes of cultural evolution. Abstract : Culture drives cognitive evolution by supporting the transmission and intergenerational accumulation of skills and knowledge, based on social learning and teaching: Later generations benefit from what their predecessors acquired. Taking a metaperspective on those experimental studies that explore the mechanisms underlying cultural transmission, Caldwell discusses their potential for generating valuable insights, their possible limitations, and their generalizability to other species.